Adjuvant Trastuzumab Emtansine Versus Paclitaxel in Combination With Trastuzumab for Stage I HER2-Positive Breast Cancer (ATEMPT): A Randomized Clinical Trial. Issue 21 (20th July 2021) - Tolaney, Sara M.; Tayob, Nabihah; Dang, Chau; Yardley, Denise A.; Isakoff, Steven J.; Valero, Vicente; Faggen, Meredith; Mulvey, Therese; Bose, Ron; Hu, Jiani; Weckstein, Douglas; Wolff, Antonio C.; et al.
Abstract : PURPOSE: The ATEMPT trial was designed to determine if treatment with trastuzumab emtansine (T-DM1) caused less toxicity than paclitaxel plus trastuzumab (TH) and yielded clinically acceptable invasive disease-free survival (iDFS) among patients with stage I human epidermal growth factor receptor 2–positive (HER2+) breast cancer (BC). METHODS: Patients with stage I centrally confirmed HER2+ BC were randomly assigned 3:1 to T-DM1 or TH and received T-DM1 3.6 mg/kg IV every 3 weeks for 17 cycles or T 80 mg/m 2 IV with H once every week × 12 weeks (4 mg/kg load →2 mg/kg), followed by H × 39 weeks (6 mg/kg once every 3 weeks). The co-primary objectives were to compare the incidence of clinically relevant toxicities (CRTs) in patients treated with T-DM1 versus TH and to evaluate iDFS in patients receiving T-DM1. RESULTS: The analysis population includes all 497 patients who initiated protocol therapy (383 T-DM1 and 114 TH). CRTs were experienced by 46% of patients on T-DM1 and 47% of patients on TH ( P = .83). The 3-year iDFS for T-DM1 was 97.8% (95% CI, 96.3 to 99.3), which rejected the null hypothesis ( P < .0001). Serially collected patient-reported outcomes indicated that patients treated with T-DM1 had less neuropathy and alopecia and better work productivity compared with patients on TH. CONCLUSION: Among patients with stage I HER2+ BC, one year of adjuvant T-DM1 was associated with excellent 3-year iDFS, but was not associated with fewer CRT compared with TH.